Perwujudan Pasal 78 Ayat (2) Undang-Undang Nomor 6 Tahun 2014 Tentang Desa Terhadap Pembangunan Desa Mulai dari Perencanaan, Pelaksanaan dan Pengawasan di Desa Sucopangepok Jember - Wildatul , Hasanah; Fauziyah (Indonesian Journal Publisher, 2025)
Nationally, village development is part of the national development policy in line with the Sustainable Development Goals (SDGs), particularly in reducing poverty, improving the quality of infrastructure, and strengthening village independence. This study aims to determine the extent to which Sucopangepok Village in Jember Regency has implemented the provisions of “Article 78 Paragraph (2) of Law No. 6/2014 on Villages” from the stages of development planning, implementation, and supervision. This method combines empirical legal studies with conceptual and legislative approaches. Data were collected through observation and interviews with stakeholders. The findings of this research show that the form of implementation of development in Sucopangepok Village, Jember Regency is carried out starting with planning through the RPJMDes, and RKPJDes and carrying out development in accordance with the planning, both budget and program, there are obstacles in the implementation of less efficient use of the budget, low community participation, and technical obstacles in project implementation. At the supervision stage, it is carried out by internal parties, namely the BPD (Village Consultative Body), and external parties from the Inspectorate (APIP), the Regional Government has not been implemented properly. This research suggests the need to optimize budget planning, increase community participation, and strengthen monitoring mechanisms to achieve sustainable development goals in Sucopangepok Village.